1993
DOI: 10.1007/bf02783805
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise and zinc supplement on the hematological parameters in rats

Abstract: This study evaluates the consequences of a session of intensive short-duration exercise and Zn supplementation on different hematological variables. Forty male Wistar rats were divided into four groups (n = 10): the first nonsupplemented, maintained at rest (R); the second nonsupplemented, undergoing exercise (E); the third supplemented with Zn, kept at rest (ZnR); and the fourth supplemented with Zn, undergoing exercise (ZnE). Zinc supplements (200 ppm) were given in drinking water. The exercise consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
6
1
1
Order By: Relevance
“…Taken together, we infer a similar response of haematological variables to regular daily training in all endotherms studied in this respect. The response to short-term exercise in zebra finches also resembles that reported for mammals (Cordova et al, 1993;Connes et al, 2006;Zobba et al, 2011), i.e. mammals likewise showed elevated Hct and Hb content immediately after exercise compared with that of individuals at rest.…”
Section: Discussionsupporting
confidence: 67%
“…Taken together, we infer a similar response of haematological variables to regular daily training in all endotherms studied in this respect. The response to short-term exercise in zebra finches also resembles that reported for mammals (Cordova et al, 1993;Connes et al, 2006;Zobba et al, 2011), i.e. mammals likewise showed elevated Hct and Hb content immediately after exercise compared with that of individuals at rest.…”
Section: Discussionsupporting
confidence: 67%
“…Some studies confirmed the results and they reported increase of Hb and HCT following consumption of zinc supplements in rats swimming in the pool. [13,27] In the present study, the amount of MCH, MCV, and MCHC was not significantly changed after injecting zinc supplements in comparison with the animals receiving no zinc. Besides, a significant change in the number of WBCs following performing physical activity was not observed.…”
Section: Discussioncontrasting
confidence: 52%
“…[8] Moreover, the number of leukocytes and thrombocytes in both groups receiving zinc supplement was not significantly changed compared to the other groups. Similarly, Cordova et al [13] and Baltaci et al [27] also reported that using zinc supplement cannot affect the number of leukocytes after physical activities. In contrast to our results, Kilic et al [28] and Polat [29] found that physical activity can increase the number of leukocytes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nesse sentido, temos observado em atletas de elite que o treinamento diário de alto nível, ao longo da temporada de competição, provoca importantes modificações no sistema imunológico, tanto em condições basais quanto após o exercício máximo. As alterações imunológicas observadas nos atletas parecem estar associadas com reduções da resistência física e do desempenho 24,25,36,44,45 .…”
Section: Iii1 Alterações Estruturais No Músculo Lesadounclassified